Value Chain Analysis of Slipper Industry in the Footwear Capital of the North - Subia, Gener Santiago; Mina, Jennilyn C; Ermita, Philip P (ExcelingTech, 2020)
This research delved at describing the slipper industry in the so called footwear capital of the North in Nueva Ecija, Philippines, the “Gapan City”. The study was anchored on the Value Chain Analysis Framework by Michael Porter. It utilized descriptive research design and involved 46 slipper manufacturers as respondents. The researchers particularly focused on the industry’s business operation in terms of inputs provision, production, marketing, cost and return analysis, prospects, problems and constraints of the slipper industry. The study revealed that raw materials were mostly from China. Worker turnover rate was high, since they were underpaid. Pricing methods employed were cost–based, penetration and customer–based pricing. The prime geographical markets of the manufactured slippers were in the City of Gapan and other nearby regions. Many of the slipper manufacturers relied on credit extended by suppliers and other financing and financial institutions, hence causing shrinkage in income. Although this business is profitable, imported slippers from other countries still haunt local slipper manufacturers which were directly competing with their products. The industry is at a standstill because of its current state enables them to harness full potentials of the product both in local and international market. Nueva